Les questions en anglais : une approche cognitive - Jérôme Puckica (Corela)
This article analyses questions in English from a Cognitive Linguistics perspective. The main kinds of question are discussed as well as the various structures used to express them: main interrogative clauses, both closed and open, tag questions, declarative questions, echo questions, and indirect questions. The intonation of questions, subject-auxiliary inversion, and the role of the auxiliary do are among the topics discussed. The sometimes subtle distinction between subordinate interrogative clauses and free relative constructions is also touched upon. The various structures which are dealt with are considered as instances of symbolic constructions with their own formal and semantic-pragmatic properties. From that perspective, grammar is not independent of meaning but instead appears to be fundamentally meaningful.